1 in 10: the diabetes crisis in men. Issue 2 (3rd April 2018) - Baker, Peter
Abstract : Diabetes has been described as a national health emergency, but the burden of the disease on men has not been fully recognised or responded to by health policymakers and practitioners. One man in 10 now has type 1 or type 2 diabetes, and a three‐fold increase in the incidence of diabetes in middle‐aged men has been predicted for the next 30 years. Peter Baker looks at the issues.